Knowledge about Essential Tremor: A Study of Essential Tremor Families - Cristal, Ashley D.; Chen, Karen P.; Hernandez, Nora Cristina; Factor-Litvak, Pam; Clark, Lorraine N.; Ottman, Ruth; Louis, Elan D. (Frontiers in Neurology, 2018)
Background Essential tremor (ET) is among the most common neurological diseases and it often runs in families. How knowledgeable ET patients and their families are about their disease has been the subject of surprisingly little scholarship. Methods To fill this gap in knowledge, we administered a comprehensive 32-item survey (i.e., questions about etiology, pathophysiology, symptoms and signs, natural history and treatments) to 427 participants, including 76 ET probands, 74 affected relatives [AFRs], 238 unaffected relatives, and 39 spouses of unaffected relatives, all of whom were participating in two ET family studies. We hypothesized that there would be gaps in knowledge about ET and furthermore, that probands and AFRs would be the most knowledgeable, followed by unaffected relatives and then spouses of unaffected relatives, who would be the least knowledgeable. Results Overall, ET patients lacked knowledge about their disease. Nearly 1/3 of probands answered “yes” or “do not know” to the question, “is ET the same or different from the type of tremor that many normal people can get when they become old and frail?” A similar proportion did not know whether children could get ET or they responded “no”. Nearly 1/4 of affecteds (i.e., probands and AFRs) did not know whether or to what degree (e.g., very well, moderately well, not well) the symptoms of ET could be medically controlled, and 38.0% either reported that there was no brain surgery for ET or reported that they did not know. Nearly 17% of affecteds did not endorse genes as a cause for ET, which was surprising given the fact that this was a family study of ET. Probands and AFRs were the most knowledgeable, followed by unaffected relatives. Spouses of unaffected relatives were the least knowledgeable. Conclusion We targeted a large group of ET patients and their families, as this group is perhaps most likely to be informed about the disease. ET patients and their affected relatives were more knowledgeable about the features of ET than their family members without ET. Overall, however, knowledge of ET was very limited and this lack of knowledge encompassed all aspects of the disease including